The Use of Palm Oil Final Effluent as Solid Soap to Support a Sustainable Economy - Kharisma, Nova (LifeSciFi, 2026)
The palm oil industry plays a vital role in Indonesia’s economy, but it also poses serious challenges due to the waste it generates. Much of this waste remains underutilized, with current efforts primarily focused on pollution control rather than generating significant economic benefits. Final effluent, as the end-of-process waste, still has the potential to be reused because it contains residual oil. This study aims to explore the utilization of final effluent as an additive in the production of bar soap, evaluate the product’s quality characteristics, and assess its potential in supporting the circular economy and increasing the industry’s value added. The study employed a laboratory experimental method using a quantitative-descriptive and comparative approach. Residual oil was extracted using an organic solvent, purified, and then formulated into solid soap via the hot process method. Evaluation was based on physical and chemical parameters. The results showed that the soap met SNI 3532:2021 standards for pH and moisture content, excelled in foam height, but free alkali still required adjustment through NaOH control. This utilization has the potential to increase the economic value of waste.